THE RELATIONSHIP BETWEEN MATERNAL AND CHILD HEALTH SERVICES AND THE INCIDENCE OF STUNTING AMONG TODDLERS AT THE SIKABU COMMUNITY HEALTH CENTER IN PADANG PARIAMAN: A CASE-CONTROL STUDY : MATERNAL AND CHILD HEALTH SERVICES - Novi Putriana Dewi; Syafrawati Syafrawati; Vivi Triana (STIKes Mandala Waluya Kendari, 2026)
Background: Stunting remains a serious public health concern in Indonesia. This study aims to examine the relationship between maternal and child health (MCH) service utilization, including antenatal care (ANC) visits, exclusive breastfeeding, complete basic immunization, vitamin A supplementation, and child growth monitoring and the incidence of stunting in children under five at at Sikabu Public Health Center, Padang Pariaman Regency, in 2025. Methods: This study used a case-control design with a 1:1 ratio, involving 154 respondents (77 cases and 77 controls). Data were obtained from E-PPBGM, Maternal Cohort Register, Nutrition Register, and Immunization Register. Analysis was conducted using Chi-Square tests and multiple logistic regression. Results: Bivariate analysis showed that incomplete ANC visits (p<0.001; OR=7.13), absence of exclusive breastfeeding (p<0.001; OR=14.1), and irregular growth monitoring (p<0.001; OR=3.92) were significantly associated with stunting. Multivariate analysis identified exclusive breastfeeding as the most dominant risk factor (Adjusted OR=18.3), followed by ANC visits (Adjusted OR=10.6) and vitamin A supplementation (p=0.03). Conclusion: Exclusive breastfeeding, ANC visits, and growth monitoring are MCH service components associated with stunting incidence, with exclusive breastfeeding as the dominant factor. Optimization of all MCH service components is essential for accelerating stunting reduction.